Analisis Kinerja Proses Administrasi Sekolah di SDI Kyai Amin Surabaya - Aprilia, Popi; Putri, Salsabilillah Rachmania; Wardani, Salwa Azelina (ARZUSIN, 2023)
School administration performance is a process that is considered important for the continuity of teaching and learning activities. This study aims to analyze the performance of the administrative process at SDI KYAI AMIN Surabaya school, because school administration is something that needs to be updated in improving the quality of education. In this study using a qualitative descriptive approach to the method of data collection observation and literature review. By asking several questions to the principal of SDI KYAI AMIN Surabaya. So that in this study data were obtained such as school administrative structure, school administrative processes, school administration reporting, routine activities carried out by administration at school, administrative supervision, as well as factors that influence the school administration process. From the results of this study, researchers will be able to find out how the performance of school administration at SDI KYAI AMIN Surabaya.